Comparative Study on Medicinal Natures (qi) of Black Ginseng, Red Ginseng, and Ginseng Leaves Based on Typical Deficiency-Heat Syndrome Rat Model. (23rd April 2022) - Wan, Mei-Yu; Liu, Lin-Lin; Dou, De-Qiang
Abstract : To elucidate the medicinal nature of black ginseng (BG) by comparison of the effects of four Chinese herbs with different medicinal natures on the deficiency-heat syndrome rat model which was established by intragastric administration of traditional Chinese drugs with hot nature, the appearance indexes, biochemical indexes, and pathological sections of thyroid and stomach were examined. In addition, the seven short-chain fatty acids (SCFAs) in rat feces were also determined by headspace gas chromatography-mass spectrometry to reveal the action mechanism of the drugs with different natures. Results indicated that all the 4 drugs could exhibit similar actions in regulating the biochemical indexes of triiodothyronine (T3), thyroxine (T4), thyrotropin-releasing hormone (TRH), thyroid-stimulating hormone (TSH), and corticosterone (CORT) representing the hypothalamus-pituitary-thyroid (HPT) and hypothalamus-pituitary-adrenal (HPA) axes of the animal. However, cold-natured cortex phellodendri (HB) and ginseng leaves (GLs) showed stronger downregulation of the AChE activity of the nervous system. Red ginseng (RG) and BG tested exhibited stronger upregulation of the liver Na + -K + -ATPase activity. Principal component analysis (PCA) showed that GLs are similar to those of HB which belongs to the cold-nature drug, whereas BG showed closer to RG which attributes to a warm-nature drug. Thus, BG could be ascribed to a warm-nature drug. Further research disclosed that RG and BG mainly regulated the acetic acid and GL and HB primarily modulated the isovaleric acid and hexanoic acid in rat feces, which could be the features of drugs with warm or cold nature on the regulation of SCFAs in rats. It is for the first time that the medicinal nature of BG and its effect on the SCFAs were examined.